Analisis Muatan Dimensi Kreatif pada Pelaksanaan Projek Penguatan Profil Pelajar Pancasila di SD Muhammadiyah 02 Kendalsari - Mufti, Neza Anissa; Purnamasari, Iin; Rofian, Rofian (CV. Supernova Office Stationary and Printing, 2023)
This study aims to analyze the content of the creative dimension in the implementation of the Pancasila Student Profile strengthening project in class IV. This research was conducted at Muhammadiyah 02 Elementary School Kendalsari in Pemalang City. In this study, the qualitative research method used was a descriptive approach and data collection techniques with observations, interviews, questionnaires or questionnaires and data cards. The results show that the content of the creative dimension in implementing the project to strengthen the Pancasila Student Profile in grade IV is in accordance with the character achievements in the elements of the creative dimension of the Pancasila Student Profile